The information system of detecting the informed activities in derivative asset tradings; The 9th International Forum on on Strategic Techology (IFOST-2014), September 21-23, 2014, Cox's Bazar, Bangladesh - Kritski O. L. Oleg Leonidovich (2014, 2014)
Title screen